Muscle Synergy-Based Functional Electrical Stimulation Reduces Muscular Fatigue in Post-Stroke Patients: A Systematic Comparison - Smriti Bala; Venugopalan Y. Vishnu; Deepak Joshi (IEEE, 2023)
Muscle synergy-based functional electrical stimulation had improved movement kinematics instantly and in long-term use in post-stroke patients. However, the therapeutic benefits and efficacy of muscle synergy-based functional electrical stimulation patterns over traditional stimulation patterns need exploration. This paper presents the therapeutic benefits of muscle synergy-based functional electrical stimulation compared to traditional stimulation patterns from the perspective of muscular fatigue and kinematic performance produced. Three stimulation waveforms/envelopes: customized rectangular, trapezoidal, and muscle synergy-based FES patterns were administered on six healthy and six post-stroke patients to achieve full elbow flexion. The muscular fatigue was measured through evoked-electromyography, and the kinematic outcome was measured through angular displacement during elbow flexion. The time domain (peak-to-peak amplitude, mean absolute value, root-mean-square) and frequency domain (mean frequency, median frequency) myoelectric indices of fatigue were calculated from evoked-electromyography. Myoelectric indices of fatigue and peak angular displacements of elbow joint were compared across waveforms. The presented study found that the muscle synergy-based stimulation pattern sustained the kinematic output for longer durations and induced less muscular fatigue followed by trapezoidal and customized rectangular patterns in healthy and post-stroke participants. These findings imply that the therapeutic effect of muscle synergy-based functional electrical stimulation stems from not only being biomimetic but also due to it being efficient in inducing less fatigue. The slope of current injection was a crucial factor in determining the performance of muscle synergy-based FES waveforms. The presented research methodology and outcomes would help researchers and physiotherapists in choosing effective stimulation patterns for maximizing post-stroke rehabilitation benefits. Note: FES waveform/ pattern/ stimulation pattern all refers to FES envelop in this paper.